8 QAM regeneration using a phase-sensitive amplifier with dual-conjugated pumps - Stiller, Birgit; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics InfoBase Conference Papers, 2013)
CRIS-Team Scopus Importer:2021-06-29

Access to acoustic decay time in photonic circuits via Brillouin-based phononic memory - Stiller, Birgit; Merklein, Moritz; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2016)
Using the principle of light storage in acoustic waves, we demonstrate the direct measurement of the acoustic decay time in an integrated photonic chip and discuss the relation to the respective Brillouin gain spectrum characterization.
CRIS-Team Scopus Importer:2021-06-29

A chip-integrated Brillouin-based optical memory - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (2017 Opto-Electronics and Communications Conference, OECC 2017 and Photonics Global Conference, PGC 2017, 2017)
Storing and delaying optical signals is key for next generation networks and computing architectures that harness Integrated optics to solve major challenges such as operational bandwidth, capacity and energy efficiency. However, the speed of light, that provides fast data transmission over long distances, becomes a challenge in integrated circuits if one needs to synchronize, reroute, buffer or process data. Therefore, a fast chip-integrated optical buffer is required. Here, we show an approach based on a coherent transfer of information from optical signals to acoustic phonons in a planar integrated circuit. We demonstrate a GHz bandwidth and the compatibility with coherent communication schemes based on amplitude and phase encoding. Furthermore, we show the possibility of advanced on-chip signal processing schemes, such as non-reciprocal light storage.
CRIS-Team Scopus Importer:2021-06-29
Keywords: (070.4340) Nonlinear optical signal processing; (190.0190) Nonlinear optics; (200.4490) Optical buffers; (290.5900) Scattering; stimulated Brillouin

A chip-integrated coherent photonic-phononic memory - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Nature Communications, 2017)
Controlling and manipulating quanta of coherent acoustic vibrations - phonons - in integrated circuits has recently drawn a lot of attention, since phonons can function as unique links between radiofrequency and optical signals, allow access to quantum regimes and offer advanced signal processing capabilities. Recent approaches based on optomechanical resonators have achieved impressive quality factors allowing for storage of optical signals. However, so far these techniques have been limited in bandwidth and are incompatible with multi-wavelength operation. In this work, we experimentally demonstrate a coherent buffer in an integrated planar optical waveguide by transferring the optical information coherently to an acoustic hypersound wave. Optical information is extracted using the reverse process. These hypersound phonons have similar wavelengths as the optical photons but travel at five orders of magnitude lower velocity. We demonstrate the storage of phase and amplitude of optical information with gigahertz bandwidth and show operation at separate wavelengths with negligible cross-talk.
CRIS-Team Scopus Importer:2021-06-29

A coherent on-chip optical memory: Storing amplitude and phase as acoustic phonons - Stiller, Birgit; Merklein, Moritz; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2016)
We demonstrate for the first time the storage of multiple phase and amplitude levels of an optical signal as coherent acoustic phonons. The storage concept is implemented on-chip with a GHz-bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Advanced Functions for Signal Processing and Sensing Harnessing On-Chip SBS - Zarifi, Atiyeh; Stiller, Birgit; Eggleton, Benjamin J. (2018 IEEE 7th International Conference on Photonics, ICP 2018, 2018)
This paper reviews some of the significant SBSenabled signal processing applications in chalcogenide photonic waveguides and demonstrates a characterization technique to monitor the performance of this platform.
CRIS-Team Scopus Importer:2021-06-29
Keywords: BOCDA; Distributed SBS sensing; Photonic integrated waveguides; Stimulated Brillouin scattering(SBS); on-chip RF signal processing

Agile and Versatile Quantum Communication: Signatures and Secrets - Richter, Stefan; Thornton, Matthew; Khan, Imran; Scott, Hannah; Jaksch, Kevin; Vogl, Ulrich; Stiller, Birgit; Leuchs, Gerd; Marquardt, Christoph; Korolkova, Natalia (Physical Review X, 2021)
Agile cryptography allows for a resource-efficient swap of a cryptographic core in case the security of an underlying classical cryptographic algorithm becomes compromised. Conversely, versatile cryptography allows the user to switch the cryptographic task without requiring any knowledge of its inner workings. In this paper, we suggest how these related principles can be applied to the field of quantum cryptography by explicitly demonstrating two quantum cryptographic protocols, quantum digital signatures (QDS) and quantum secret sharing (QSS), on the same hardware sender and receiver platform. Crucially, the protocols differ only in their classical postprocessing. The system is also suitable for quantum key distribution (QKD) and is highly compatible with deployed telecommunication infrastructures, since it uses standard quadrature phase-shift keying encoding and heterodyne detection. For the first time, QDS protocols are modified to allow for postselection at the receiver, enhancing protocol performance. The cryptographic primitives QDS and QSS are inherently multipartite, and we prove that they are secure not only when a player internal to the task is dishonest, but also when (external) eavesdropping on the quantum channel is allowed. In our first proof-of-principle demonstration of an agile and versatile quantum communication system, the quantum states are distributed at GHz rates. A 1-bit message may be securely signed using our QDS protocols in less than 0.05 ms over a 2-km fiber link and in less than 0.2 s over a 20-km fiber link. To our knowledge, this also marks the first demonstration of a continuous-variable direct QSS protocol.
CRIS-Team Scopus Importer:2021-03-19

All-optical nonlinear activation function based on stimulated Brillouin scattering - Slinkov, Grigorii; Becker, Steven; Englund, Dirk; Stiller, Birgit (Nanophotonics, 2025)
Optical neural networks have demonstrated their potential to overcome the computational bottleneck of modern digital electronics. However, their development towards high-performing computing alternatives is hindered by one of the optical neural networks’ key components: the activation function. Most of the reported activation functions rely on opto-electronic conversion, sacrificing the unique advantages of photonics, such as resource-efficient coherent and frequency-multiplexed information encoding. Here, we experimentally demonstrate a photonic nonlinear activation function based on stimulated Brillouin scattering. It is coherent and frequency selective and can be tuned all-optically to take LEAKYRELU, SIGMOID, and QUADRATIC shape. Our design compensates for the insertion loss automatically by providing net gain as high as 20 dB, paving the way for deep optical neural networks.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Brillouin scattering; nonlinear activation function; nonlinear optics; optical fiber; optical neural network; optoacoustics; photonic neuromorphic computing

All-optical signal regeneration of advanced modulation formats - Röthlingshöfer, Tobias; Richter, Thomas; Stiller, Birgit; Onishchukov, Georgy; Schubert, Colja; Schmauß, Bernhard; Leuchs, Gerd (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIII, 2014)
With growing demand on transmission capacity, spectral-efficient multilevel modulation formats such as quadrature amplitude modulation (QAM) become of great interest. One of their weaknesses is high sensitivity to noise accumulation, especially in long-haul transmission systems. Our investigations have shown the possibility of all-optical regeneration of multiple amplitude and phase states. Processing of amplitude noise in several amplitude states is based on periodicity of interference conditions in modified nonlinear fiber Sagnac interferometers. Their staircase-like power transfer characteristic can be used for phase-preserving amplitude regeneration of multiple amplitude states. Processing of QAM with up to three non-zero amplitude states, e.g. 16QAM, has been demonstrated in numerical simulations. Furthermore, simultaneous amplitude regeneration of a star-8QAM format with two amplitude states was performed experimentally. Recently, it has also been shown that phase-sensitive amplification for multiple phase states can be realized in fiber optical parametric amplifiers using four-wave mixing (FWM) with a high-order idler. Our numerical simulations and experimental results for star-8QAM revealed that with some modifications, this approach can be used not only for reduction of phase noise in multilevel phase-shift keying but also for signals with multiple amplitude states. The transmission improvement using a cascade of these two regenerator types has been demonstrated in numerical simulations and experiments. Numerical investigations confirm also the possibility to combine both approaches in a single device by using the highly nonlinear fiber in the Sagnac interferometer loop simultaneously for phase-sensitive amplification in one propagation direction. © (2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use onl
lhft_intern.bib::Roethlingshoefer2014_8

An on-chip multi-wavelength photonic-phononic memory - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We demonstrate the first integrated multi-wavelength photonic-phononic memory. The memory is based on stimulated Brillouin scattering and enables the storage of light pulses as acoustic phonons up to the acoustic lifetime.
CRIS-Team Scopus Importer:2021-06-29

An optoacoustic field-programmable perceptron for recurrent neural networks - Becker, Steven; Englund, Dirk; Stiller, Birgit (Nature Communications, 2024)
Recurrent neural networks (RNNs) can process contextual information such as time series signals and language. But their tracking of internal states is a limiting factor, motivating research on analog implementations in photonics. While photonic unidirectional feedforward neural networks (NNs) have demonstrated big leaps, bi-directional optical RNNs present a challenge: the need for a short-term memory that (i) programmable and coherently computes optical inputs, (ii) minimizes added noise, and (iii) allows scalability. Here, we experimentally demonstrate an optoacoustic recurrent operator (OREO) which meets (i, ii, iii). OREO contextualizes the information of an optical pulse sequence via acoustic waves. The acoustic waves link different optical pulses, capturing their information and using it to manipulate subsequent operations. OREO’s all-optical control on a pulse-by-pulse basis offers simple reconfigurability and is used to implement a recurrent drop-out and pattern recognition of 27 optical pulse patterns. Finally, we introduce OREO as bi-directional perceptron for new classes of optical NNs.
CRIS-Team Scopus Importer:2024-04-26

Attacks on practical quantum key distribution systems (and how to prevent them) - Jain, Nitin; Stiller, Birgit; Khan, Imran; Elser, Dominique Alexander; Marquardt, Christoph; Leuchs, Gerd (Contemporary Physics, 2016)
With the emergence of an information society, the idea of protecting sensitive data is steadily gaining importance. Conventional encryption methods may not be sufficient to guarantee data protection in the future. Quantum key distribution (QKD) is an emerging technology that exploits fundamental physical properties to guarantee perfect security in theory. However, it is not easy to ensure in practice that the implementations of QKD systems are exactly in line with the theoretical specifications. Such theory–practice deviations can open loopholes and compromise security. Several such loopholes have been discovered and investigated in the last decade. These activities have motivated the proposal and implementation of appropriate countermeasures, thereby preventing future attacks and enhancing the practical security of QKD. This article introduces the so-called field of quantum hacking by summarising a variety of attacks and their prevention mechanisms.
CRIS-Team Scopus Importer:2021-06-29
Keywords: countermeasures; practical data security; quantum computer; Quantum cryptography; quantum hacking; quantum key distribution

Black-light continuum generation in a silica-core photonic crystal fiber - Sylvestre, Thibaut; Ragueh, A. R.; Lee, M. W.; Stiller, Birgit; Fanjoux, G.; Barviau, Benoit; Mussot, Arnaud; Kudlinski, Alexandre (Optics Letters, 2012)
We report the observation of a broadband continuum spanning from 350 to 470 nm in the black-light region of the electromagnetic spectrum as a result of picosecond pumping a solid-core silica photonic crystal fiber at 355 nm. This was achieved despite strong absorption and a large normal dispersion of silica glass in the UV. Further investigations reveal that the continuum generation results from the interplay of intermodally phase-matched fourwave mixing and cascaded Raman scattering. Wealso discuss the main limitations intermsof bandwidth and power due to temporal walk-off, fiber absorption, and the photo darkening effect, and we suggest simple solutions. © 2012 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29

Brillouin-based light storage and delay techniques - Merklein, Moritz; Stiller, Birgit; Eggleton, B. J. (Journal of Optics, 2018)
Storing or delaying optical signals is of key interest for fundamental research and applications in radar, microwave signal processing, quantum information as well as optical communication systems. Delay systems based on stimulated Brillouin scattering (SBS), a coherent interaction between optical and acoustic waves can be implemented in optical fiber or chip-scale platforms, operate at room temperature and can be fully controlled via the optical pump wave. In this article, we review delay and storage techniques based on SBS. We present SBS slow-light, fiber delay lines based on Brillouin dynamic gratings, Brillouin quasi-light storage and Brillouin-based light storage via photon-phonon conversion and compare their performance. In this process, we also include an overview of different platforms used for Brillouin light storage and delay schemes, such as optical fiber, planar soft-glass waveguides, and silica fiber-tip resonators.
CRIS-Team Scopus Importer:2021-06-29
Keywords: light storage; nonlinear optics; optical delay; optical signal processing; photonics; slow-light; stimulated Brillouin scattering

Brillouin-based light storage of 200ps-long pulses for 70 pulse widths - Jaksch, Kevin; Merklein, Moritz; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J.; Stiller, Birgit (Optics InfoBase Conference Papers, 2017)
We experimentally demonstrate the storage of optical pulses (200ps-long, eight amplitude levels) on a photonic chip for over 70 pulse widths with minimum distortions in pulse shape and width using a Brillouin-based memory.
CRIS-Team Scopus Importer:2021-06-29

Brillouin-Based Storage of QPSK Signals with Fully Tunable Phase Retrieval - Saffer, Olivia; Cabello, Jesús Humberto Marines; Becker, Steven; Geilen, Andreas; Stiller, Birgit (2025 Conference on Lasers and Electro-Optics, CLEO 2025, 2025)
Photonic memory is an important building block for all-optical information processing. We experimentally demonstrate storage of quadrature phase-encoded data at ambient and cryogenic temperatures and show all-optical, fully-tunable control of the re-trieved optical phase.
CRIS-Team Scopus Importer:2025-11-28

Brillouin-based storage of QPSK signals with fully tunable phase retrieval - Saffer, Olivia; Marines Cabello, Jesús Humberto; Becker, Steven; Geilen, Andreas; Stiller, Birgit (APL Photonics, 2025)
Photonic memory is an important building block to delay, route, and buffer optical information, for instance, in optical interconnects or for recurrent optical signal processing. Photonic-phononic memory based on stimulated Brillouin-Mandelstam scattering (SBS) has been demonstrated as a coherent optical storage approach with broad bandwidth, frequency selectivity, and intrinsic nonreciprocity. Here, we experimentally demonstrate the storage of quadrature-phase encoded data at room temperature and at cryogenic temperatures. We store and retrieve the 2-bit states 00, 01, 10, 11 encoded as optical pulses with the phases 0 , π/2 , π , 3π/2 —a quadrature phase shift keying signal. The 2-bit signals are retrieved from the acoustic domain with a global phase rotation of π, which is inherent in the process due to SBS. We also demonstrate full phase control over the retrieved data based on two different handles: by detuning slightly from the SBS resonance or by changing the storage time in the memory scheme, we can cover the full range [0, 2π). At a cryogenic temperature of 3.9 K, we have increased readout efficiency as well as gained access to longer storage times, which results in a detectable signal at 140 ns. All in all, the work sets the cornerstone for optoacoustic memory schemes with phase-encoded data.
CRIS-Team Scopus Importer:2025-07-11

Brillouin echo-distributed sensing based on differential phase-shift keying technique - Lee, Min Won; Stiller, Birgit; Hauden, Jérôme; Maillotte, Hervé; Thévenaz, Luc; Sylvestre, Thibaut (European Conference on Optical Communication, ECOC, 2011)
In this letter, we demonstrate experimentally Brillouin echo-distributed sensing based on differential phase-shift keying technique. A positive and negative pulse is applied to a single Mach-Zehnder modulator to achieve a resolution of 5 cm. © 2011 OSA.
CRIS-Team Scopus Importer:2021-06-29

Brillouin-enhanced four-wave mixing with optical chiral states - Zeng, Xinglin; Stiller, Birgit (APL Photonics, 2025)
Brillouin-enhanced four-wave mixing (BE-FWM)—also known as Brillouin dynamic gratings—is an important nonlinear effect in photonics that couples four light waves by traveling acoustic waves. The effect has received much attention in the past few decades, especially for applications in fiber sensing, signal processing, and optical delay lines. Here, we report BE-FWM with optical chiral states (i.e., circular polarization and vortex states) in twisted photonic crystal fiber, by leveraging the topology-selective Brillouin effect. Phase-matching has the consequence that the traveling acoustic gratings created by circularly polarized vortex pump and Stokes in the stimulated Brillouin scattering can be used to modulate a frequency-shifted probe, where the pump/Stokes and probe have different circular polarization or topological charges. Based on our findings, we demonstrate cross-frequency selective information transfer and show that the information is transferred only when pump and probe have opposite circular polarization.
CRIS-Team Scopus Importer:2025-08-01

Brillouin spectroscopy of a hybrid silicon-chalcogenide waveguide with geometrical variations - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Liu, Yang; Morrison, Blair; Casas-Bedoya, Alvaro; Ren, Guanghui; Nguyen, Thach G.; Vu, Khu; Choi, Duk-Yong; Mitchell, Arnan; Madden, Steven J.; et al. (Optics Letters, 2018)
Recent advances in design and fabrication of photonic-phononic waveguides have enabled stimulated Brillouin scattering in silicon-based platforms such as underetched silicon waveguides and hybrid waveguides. Due to the sophisticated design and, more importantly, high sensitivity of the Brillouin resonances to geometrical variations in micro- and nano-scale structures, it is necessary to have access to the localized opto-acoustic response along those waveguides to monitor their uniformity and maximize their interaction strength. In this Letter, we design and fabricate photonic-phononic waveguides with a deliberate width variation on a hybrid silicon-chalcogenide photonic chip and confirm the effect of the geometrical variation on the localized Brillouin response using a distributed Brillouin measurement.
CRIS-Team Scopus Importer:2021-06-29

Cascaded forward Brillouin scattering to all Stokes orders - Wolff, Christian; Stiller, Birgit; Eggleton, B. J.; Steel, M. J.; Poulton, C. G. (New Journal of Physics, 2017)
Inelastic scattering processes such as Brillouin scattering can often function in cascaded regimes and this is likely to occur in certain integrated opto-acoustic devices. We develop a Hamiltonian formalism for cascaded Brillouin scattering valid for both quantum and classical regimes. By regarding Brillouin scattering as the interaction of a single acoustic envelope and a single optical envelope that covers all Stokes and anti-Stokes orders, we obtain a compact model that is well suited for numerical implementation, extension to include other optical nonlinearities or short pulses, and application in the quantum-optics domain. We then theoretically analyze intra-mode forward Brillouin scattering (FBS) for arbitrary waveguides with and without optical dispersion. In the absence of optical dispersion, we find an exact analytical solution. With a perturbative approach, we furthermore solve the case of weak optical dispersion. Our work leads to several key results on intra-mode FBS. For negligible dispersion, we show that cascaded intra-mode FBS results in a pure phase modulation and discuss how this necessitates specific experimental methods for the observation of fiber-based and integrated FBS. Further, we discuss how the descriptions that have been established in these two classes of waveguides connect to each other and to the broader context of cavity opto-mechanics and Raman scattering. Finally, we draw an unexpected striking similarity between FBS and discrete diffraction phenomena in waveguide arrays, which makes FBS an interesting candidate for future research in quantum-optics.
CRIS-Team Scopus Importer:2021-06-29
Keywords: nano-photonics; opto-mechanics; stimulated Brillouin scattering

Cascaded waveguide-based photon-phonon memory - Stiller, Birgit; Merklein, Moritz; Wolff, Christian; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Cavity-less Brillouin strong coupling in a solid-state continuous system - Martínez, Laura Blázquez; Zhu, Changlong; Stiller, Birgit (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
A strongly coupled system can coherently transfer energy between two states before it decoheres. This is a prerequisite to have quantum coherent control over a system. In the context of optomechanics, light has successfully been strongly coupled to discrete mechanical resonances of an optomechanical cavity [1]. In this work, we present the first experimental realization of cavity-free strong coupling between groups of photons and phonons in a continuous optoacoustic system. This work can path the way to optical-fiber-based and chip-integrated quantum optoacoustic control for application to photon-phonon entanglement and quantum memory.
CRIS-Team Scopus Importer:2025-09-26

Chalcogenide optical waveguides with extremely high stimulated brillouin scattering gain for integrated devices - Vu, Khu; Choi, Duk; Ma, Pan; Morrison, Blair; Stiller, Birgit; Choudhary, Amol; Eggleton, Benjamin J.; Madden, Steve (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Classically entangled optical beams for high-speed kinematic sensing - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, Marco; Giacobino, Elisabeth; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optica, 2015)
Tracking the kinematics of fast-moving objects is an important diagnostic tool for science and engineering. Here, we demonstrate an approach to positional and directional sensing based on the concept of classical entanglement in vector beams of light [Found. Phys. 28, 361–374 (1998)]. The measurement principle relies on the intrinsic correlations existing in such beams between transverse spatial modes and polarization. The latter can be determined from intensity measurements with only a few fast photodiodes, greatly outperforming the bandwidth of current CCD/CMOS devices. In this way, our setup enables two-dimensional real-time sensing with temporal resolution in the GHz range. We expect the concept to open up new directions in metrology and sensing.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Classical and quantum physics; Optical sensing and sensors

Coherently refreshing hypersonic phonons for light storage - Stiller, Birgit; Merklein, Moritz; Wolff, Christian; Vu, Khu; Ma, Pan; Madden, Steve J.; Eggleton, Benjamin J. (Optica, 2020)
Acoustic waves can serve as memory for optical information; however, propagating acoustic phonons in the gigahertz (GHz) regime decay on the nanosecond time scale. Usually this is dominated by intrinsic acoustic loss due to inelastic scattering of the acoustic waves and thermal phonons. Here we show a way to counteract the intrinsic acoustic decay of the phonons in a waveguide by resonantly reinforcing the acoustic wave via synchronized optical pulses. We experimentally demonstrate coherent on-chip storage in amplitude and phase up to 40 ns, 4 times the intrinsic acoustic lifetime in the waveguide. Through theoretical considerations, we anticipate that this concept allows for storage times up to microseconds within realistic experimental limitations while maintaining a GHz bandwidth of the optical signal.
CRIS-Team Scopus Importer:2021-06-29

Coherent photonic-phononic interactions in integrated circuits - Stiller, Birgit; Merklein, Moritz; Eggleton, Benjamin J. (23rd Opto-Electronics and Communications Conference, OECC 2018, 2018)
Using stimulated Brillouin scattering, we experimentally demonstrate a coherent storage concept that is suitable for multiple optical wavelengths and storage of 200ps-long optical pulses for over 70 pulse widths.
CRIS-Team Scopus Importer:2021-06-29

Coherent photon-phonon conversion in integrated circuits - Stiller, Birgit; Merklein, Moritz; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2017)
We experimentally demonstrate multiple conversions of information between the optical and acoustic domain. We show the coherent acousto-optic transfer by retrieving multiple amplitude and phase levels with GHz bandwidth and demonstrate multi-wavelength operation.
CRIS-Team Scopus Importer:2021-06-29

Cross talk-free coherent multi-wavelength Brillouin interaction - Stiller, Birgit; Merklein, Moritz; Vu, Khu; Ma, Pan; Madden, Stephen J.; Poulton, Christopher G.; Eggleton, Benjamin J. (APL Photonics, 2019)
Stimulated Brillouin scattering drives a coherent interaction between optical signals and acoustic phonons and can be used for storing optical information in acoustic waves. An important consideration arises when multiple optical frequencies are simultaneously employed in the Brillouin process: in this case, the acoustic phonons that are addressed by each optical wavelength can be separated by frequencies far smaller than the acoustic phonon linewidth, potentially leading to cross talk between the optical modes. Here we extend the concept of Brillouin-based light storage to multiple wavelength channels. We experimentally and theoretically show that the accumulated phase mismatch over the length of the spatially extended phonons allows each optical wavelength channel to address a distinct phonon mode, ensuring negligible cross talk and preserving the coherence, even if the phonons overlap in frequency. This phase-mismatch for broad-bandwidth pulses has far-reaching implications allowing dense wavelength multiplexing in Brillouin-based light storage, multifrequency Brillouin sensing and lasing, parallel microwave processing, and quantum photon-phonon interactions.
CRIS-Team Scopus Importer:2021-06-29

Deep recurrent neural networks operations based on stimulated Brillouin scattering - Becker, Steven; Cabello, Jesús Humberto Marines; Englund, Dirk; Stiller, Birgit (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We experimentally demonstrate eight layers of a recurrent operator for photonic neural networks using stimulated Brillouin scattering. The programmable optoacoustic building block captures and processes coherently and frequency-selectively information without relying on artificial reservoirs.
CRIS-Team Scopus Importer:2024-10-04

Demonstration of polarization pulling in a fiber-optical parametric amplifier - Stiller, Birgit; Morin, Ph; Nguyen, D. M.; Fatome, J.; Maillotte, H.; Pitois, S.; Sylvestre, T. (Optics InfoBase Conference Papers, 2012)
We report the experimental demonstration of all-optical polarization pulling of an initially polarization-scrambled signal using a fiber-optical parametric amplifier. Nonlinear polarization pulling has been achieved for both the signal and idler with 25 dB gain. © 2012 OSA.
CRIS-Team Scopus Importer:2021-06-29

Demonstration of polarization pulling using a fiber-optic parametric amplifier - Stiller, Birgit; Morin, P.; Nguyen, D. M.; Fatome, Julien; Pitois, S.; Lantz, E.; Maillotte, H.; Menyuk, C. R.; Sylvestre, Thibaut (Optics Express, 2012)
We report the observation of all-optical polarization pulling of an initially polarization-scrambled signal using parametric amplification in a highly nonlinear optical fiber. Broadband polarization pulling has been achieved both for the signal and idler waves with up to 25 dB gain using the strong polarization sensitivity of parametric amplifiers. We further derive the probability distribution function for the final polarization state, assuming a randomly polarized initial state, and we show that it agrees well with the experiments. © 2012 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29

Depolarized guided acoustic wave Brillouin scattering in hollow-core photonic crystal fibers - Zhong, Wenjia; Stiller, Birgit; Elser, Dominique Alexander; Heim, Bettina; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2015)
By performing quantum-noise-limited optical heterodyne detection, we observe polarization noise in light after propagation through a hollow-core photonic crystal fiber (PCF). We compare the noise spectrum to the one of a standard fiber and find an increase of noise even though the light is mainly transmitted in air in a hollow-core PCF. Combined with our simulation of the acoustic vibrational modes in the hollow-core PCF, we are offering an explanation for the polarization noise with a variation of guided acoustic wave Brillouin scattering (GAWBS). Here, instead of modulating the strain in the fiber core as in a solid core fiber, the acoustic vibrations in hollow-core PCF influence the effective refractive index by modulating the geometry of the photonic crystal structure. This induces polarization noise in the light guided by the photonic crystal structure.
CRIS-Team Scopus Importer:2021-06-29

Differential phase-shift-keying technique-based brillouin echo-distributed sensing - Lee, Min Won; Stiller, Birgit; Hauden, Jerome; Maillotte, Herve; Roch, Carole; Thevenaz, Luc; Sylvestre, Thibaut (IEEE Photonics Technology Letters, 2012)
In this letter, we experimentally demonstrate Brillouin echoes-based distributed optical fiber sensing with centimeter spatial resolution. It is based on a differential phase-shift-keying technique using a single Mach-Zehnder modulator to generate a pump pulse and a π-phase-shifted pulse with an easy and accurate adjustment of delay. The results are compared to those obtained in standard Brillouin echo-distributed sensing system with two optical modulators and clearly show a resolution of 5 cm in a spliced segment between two fibers by applying a π-phase-shifted pulse of 500 ps. © 2011 IEEE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin echo-distributed sensing; Brillouin optical time-domain analysis

Distributed brillouin fiber sensor with enhanced sensitivity based on anti-stokes single-sideband suppressed-carrier modulation - Duc Minh Nguyen,; Stiller, Birgit; Lee, Min Won; Beugnot, Jean-Charles; Maillotte, Herve; Mottet, Alexandre; Hauden, Jerome; Sylvestre, Thibaut (IEEE Photonics Technology Letters, 2013)
We demonstrate an alternative technique to reduce pump depletion and to improve sensitivity in the long-range Brillouin optical time-domain analysis (BOTDA) sensor. Our BOTDA system uses an anti-Stokes single-sideband suppressed-carrier modulation technique that balances the pump depletion due to fiber loss. With this technique, we show both numerically and experimentally a great improvement compared to the dual sideband standard technique. © 2012 IEEE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin optical time domain analysis; fiber optic sensor; single-sideband modulation

Distributed brillouin scattering measurement with sub-mm spatial resolution - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2017)
We report a highly localized SBS response with 780 μm spatial resolution in an As2S3 photonic integrated waveguide. This approach is used to characterize the waveguide based on its acousto-optic properties.
CRIS-Team Scopus Importer:2021-06-29

Distributed SBS sensing in a silicon-chalcogenide platform - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Liu, Yang; Morrison, Blair; Casas-Bedoya, Alvaro; Ren, Guanghui; Mitchell, Arnan; Vu, Khu; Madden, Steven J.; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2018)
We report a distributed Brillouin scattering measurement in a silicon-chalcogenide hybrid platform with a controlled width variation. We confirm 2 mm spatial resolution using Brillouin optical correlation domain analysis (BOCDA) technique in the waveguide.
CRIS-Team Scopus Importer:2021-06-29

Dynamic Brillouin cooling for continuous optomechanical systems - Zhu, Chang Long; Stiller, Birgit (Materials for Quantum Technology, 2023)
Up until now, ground state cooling using optomechanical interaction is realized in the regime where optical dissipation is higher than mechanical dissipation. Here, we demonstrate that optomechanical ground state cooling in a continuous optomechanical system is possible by using backward Brillouin scattering while mechanical dissipation exceeds optical dissipation which is the common case in optical waveguides. The cooling is achieved in an anti-Stokes backward Brillouin process by modulating the intensity of the optomechanical coupling via a pulsed pump to suppress heating processes in the strong coupling regime. With such dynamic modulation, a significant cooling factor can be achieved, which can be several orders of magnitude lower than for the steady-state case. This modulation scheme can also be applied to Brillouin cooling generated by forward intermodal Brillouin scattering.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Brillouin scattering; mechanical cooling; optomechanics; quantum optics

Dynamic Brillouin cooling for continuous optomechanical systems - Zhu, Changlong; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Cooling a mechanical oscillator to its quantum ground state by overcoming the effects of thermal environment has always attracted great interests [1-3]. Preparing a single mode mechanical oscillator to its ground state has been realized in cavity optomechanics by using sideband cooling. Beyond the cooling of single mode mechanical mode, lots of novel phonon cooling methods for multimode have been proposed recently for extended optomechanical platforms with many degrees of freedom. The intriguing limit of these cases is quantum ground state cooling in continuous optomechanical systems. Brillouin-based technologies provide cooling for groups of phonons in continuous optomechanical systems [4,5]. However, the large mechanical loss, which exceeds optical loss, limits the optomechanical continuum cooling. For general backward Brillouin scattering with higher frequency and thus lower Q-factor, it was thought that it is impractical for ground-state cooling in continuous optomechanical systems.
CRIS-Team Scopus Importer:2024-12-16

Eavesdropper localization for quantum and classical channels via nonlinear scattering - Popp, Alexandra; Sedlmeir, Florian; Stiller, Birgit; Marquardt, Christoph (Optica Quantum, 2024)
Optical fiber networks are part of the important critical infrastructure and known to be prone to eavesdropping attacks. Hence, cryptographic methods have to be used to protect communication. Quantum key distribution (QKD), at its core, offers information theoretical security based on the laws of physics. In deployments, one has to take into account practical security and resilience. The latter includes the localization of a possible eavesdropper after an anomaly has been detected by the QKD system to avoid denial-of-service. Here, we present an approach to eavesdropper location that can be employed in quantum as well as classical channels using stimulated Brillouin scattering. The tight localization of the acoustic wave inside the fiber channel using correlated pump and probe waves allows discovery of the coordinates of a potential threat within centimeters. We demonstrate that our approach outperforms conventional optical time-domain reflectometry (OTDR) in the task of localizing an evanescent outcoupling of 1% with centimeter precision inside standard optical fibers. The system is furthermore able to clearly distinguish commercially available standard SMF28 from different manufacturers, paving the way for fingerprinted fibers in high-security environments.<br

Effect of inhomogeneities on backward and forward Brillouin scattering in Photonic Crystal Fibers - Stiller, Birgit; Delque, Michael; Lee, Minw.; Mafang, Stella Foaleng; Beugnot, Jean-Charles; Kudlinski, Alexandre; Thevenaz, Luc; Maillotte, Herve; Sylvestre, Thibaut (Proceedings of SPIE - The International Society for Optical Engineering, 2010)
Photonic Crystal Fibers (PCF) play a crucial role for fundamental investigations such as acousto-optical interactions as well as for applications, such as distributed sensors. One limiting factor for these experiments is the fiber inhomogeneity owing to the drawing process. In this paper we study the effect of structural irregularities on both the backward and forward Brillouin scattering by comparing two PCFs drawn with different parameters, in order to minimize diameter fluctuations. We fully characterize their Brillouin properties including the backward Brillouin spectrum, the Brillouin threshold, a distributed measurement along the fibers and polarized Guided Acoustic Wave Brillouin Scattering (GAWBS). In the Brillouin spectrum we observe a single peak as in a single-mode fiber whereas former investigations have often shown a multiple peak spectrum in PCFs with small core. The theoretical and experimental values for the Brillouin threshold are in good agreement, which results from the single peak spectrum. By using a Brillouin echoes distributed sensing system (BEDS), we also investigate the Brillouin spectrum along the fiber with a high spatial resolution of 30 cm. Our results reveal a clear-cut difference between the distributed measurements in the two fibers and confirm the previous experiments. In the same way the GAWBS allows us to estimate the uniformity of the fibers. The spectra show a main peak at about 750 MHz, in accordance with theoretical simulations of the acoustic mode and of the elasto-optical coefficient. The fiber inhomogeneity impacts on the stability and the quality factor of the measured GAWBS spectra. We finally show that the peak frequency of the trapped acoustic mode is more related to the optical effective area rather than the core diameter of the PCF. Thus measuring the main GAWBS peak can be applied for the precise measurement of the effective area of PCFs. © 2010 SPIE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin scattering; Distributed sensing; Photonic Crystal Fibers

Efficient microwave to optical photon conversion: An electro-optical realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G. L. (Optica, 2016)
Linking classical microwave electrical circuits to the optical telecommunication band is at the core of modern communication. Future quantum information networks will require coherent microwave-to-optical conversion to link electronic quantum processors and memories via low-loss optical telecommunication networks. Efficient conversion can be achieved with electro-optical modulators operating at the single microwave photon level. In the standard electro-optic modulation scheme, this is impossible because both up- and down-converted sidebands are necessarily present. Here, we demonstrate true single-sideband up- or down-conversion in a triply resonant whispering gallery mode resonator by explicitly addressing modes with asymmetric free spectral range. Compared to previous experiments, we show a 3 orders of magnitude improvement of the electro-optical conversion efficiency, reaching 0.1% photon number conversion for a 10 GHz microwave tone at 0.42 mW of optical pump power. The presented scheme is fully compatible with existing superconducting 3D circuit quantum electrodynamics technology and can be used for nonclassical state conversion and communication. Our conversion bandwidth is larger than 1 MHz and is not fundamentally limited.
CRIS-Team Scopus Importer:2021-06-29

Efficient single sideband microwave to optical conversion using a LiNbO3 WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dimitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We present a coherent microwave to telecom signal converter based on the electro-optical effect using a crystalline WGM-resonator coupled to a 3D microwave cavity, achieving high photon conversion efficiency of 0.1% with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Erratum: Author Correction: A chip-integrated coherent photonic-phononic memory (Nature communications (2017) 8 1 (574)) - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Nature Communications, 2018)
The original version of this Article omitted the Acknowledgements section:"This work was sponsored by the Australian Research Council (ARC) Laureate Fellowship (FL120100029) and the Centre of Excellence program (CUDOS CE110001010). We acknowledge the support of the ANFF ACT."This has now been corrected in both the PDF and HTML versions of the Article.
CRIS-Team Scopus Importer:2021-06-29

Experimental observation of brillouin linewidth broadening and decay time in photonic crystal fiber - Beugnot, J. C.; Stiller, Birgit; Foaleng Mafang, S.; Lee, M. W.; Delque, M.; Kudlinski, A.; Maillotte, H.; Laude, V.; Thevenaz, L.; Sylvestre, T. (European Conference on Optical Communication, ECOC, 2010)
We present a novel distributed sensing technique that makes possible the observation of Brillouin gain spectral distribution and acoustic decay time in photonic crystal fiber as well as in standard single-mode fiber. ©2010 IEEE.
CRIS-Team Scopus Importer:2021-06-29

Extreme thermodynamics in nanolitre volumes through stimulated Brillouin–Mandelstam scattering - Geilen, Andreas; Popp, Alexandra; Das, Debayan; Junaid, Saher; Poulton, Christopher G.; Chemnitz, Mario; Marquardt, Christoph; Schmidt, Markus A.; Stiller, Birgit (Nature Physics, 2023)
Examining the physical properties of materials—particularly of toxic liquids—under a wide range of thermodynamic states is a challenging problem due to the extreme conditions the material has to experience. Such temperature and pressure regimes, which result in a change in the refractive index and sound velocity, can be accessed by optoacoustic interactions such as Brillouin–Mandelstam scattering. Here we demonstrate the Brillouin–Mandelstam measurements of nanolitre volumes of liquids in extreme thermodynamic regimes. This is enabled by a fully sealed liquid-core optical fibre containing carbon disulfide. Within this waveguide, which exhibits tight optoacoustic confinement and a high Brillouin gain, we are able to conduct spatially resolved measurements of the local Brillouin response, giving us access to a resolved image of the temperature and pressure values along the liquid channel. We measure the material properties of the liquid core at very large positive pressures (above 1,000 bar) and substantial negative pressures (below –300 bar), as well as explore the isobaric and isochoric regimes. The extensive thermodynamic control allows the tunability of the Brillouin frequency shift of more than 40% using only minute volumes of liquid.
CRIS-Team Scopus Importer:2023-10-06

Fiber optical parametric polarizer - Stiller, Birgit; Morin, Ph; Fatome, J.; Pitois, S.; Menyuk, C. R.; Sylvestre, T. (Optics InfoBase Conference Papers, 2013)
CRIS-Team Scopus Importer:2021-06-29

Fiber optic Brillouin distributed sensing using phase-shift keying modulation techniques - Stiller, Birgit; Lee, Min W.; Duc Minh Nguyen,; Hauden, Jerome; Mottet, Alexandre; Maillotte, Herve; Sylvestre, Thibaut (Proceedings of SPIE - The International Society for Optical Engineering, 2012)
In this work we demonstrate two new BOTDA sensing systems based on differential (DPSK) and quadrature (QPSK) phase-shift keying modulation techniques with enhanced performances. First we demonstrate Brillouin echoes distributed sensing (BEDS) with centimeter resolution using a single intensity DPSK modulator for the pump pulse. The optical π-phase pulse is directly generated at the end of an intensity pulse using DPSK technique. This allows an easy adjustment of the delay between the intensity and phase pulse and improves the optical loss of the pump. The second technique uses an optical QPSK modulator (I & Q modulator) as a single sideband (SSB) modulator. The advantage of I & Q modulator compared to dual-drive modulator lies on the high performance of carrier suppression of 55 dB as well as side-mode suppression of 40 dB at 1535 nm. Besides the filter that chooses either the Stokes or anti-Stokes component before detecting the Brillouin response on the photodiode is no more needed. By use of the I & Q modulator the performance of BOTDA using either Stokes or anti-Stokes component is shown and discussed. © 2012 SPIE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin optical time-domain analysis; Distributed fiber sensors; Stimulated Brillouin scattering

Frequency conversion of vortex states by chiral flexural acoustic phonons - Zeng, Xinglin; Russell, Philip S.T.J.; Stiller, Birgit (Photonics Research, 2025)
An object or system is said to be chiral if it cannot be superimposed on its mirror reflection. Chirality is ubiquitous in nature, for example, in protein molecules and chiral phonons—acoustic waves carrying angular momentum—which are usually either intrinsically present or magnetically excited in suitable materials. Here, we report the use of intervortex forward Brillouin scattering to optically excite chiral flexural phonons in a twisted photonic crystal fiber, which is itself a chiral material capable of robustly preserving circularly polarized optical vortex states. The phonons induce a spatiotemporal rotating linear birefringence that acts back on the optical vortex modes, coupling them together. We demonstrate intervortex frequency conversion under the mediation of chiral flexural phonons and show that, for the same phonons, backward and forward intervortex conversion occurs at different wavelengths. The results open up, to our knowledge, new perspectives for Brillouin scattering and the chiral flexural phonons offer new opportunities for vortex-related information processing and multi-dimensional vectorial optical sensing.
CRIS-Team Scopus Importer:2025-07-11

Frequency conversion of vortex states via chiral forward Brillouin scattering - Zeng, Xinglin; Stiller, Birgit (Frontiers in Optics: Proceedings Frontiers in Optics + Laser Science 2023, FiO, LS 2023, 2023)
We report frequency conversion of vortex states mediated by chiral flexural phonons in inter-vortex forward Brillouin scattering. The conversion allows the angular momenta of the converted waves to be coherently linked to the original signals.
CRIS-Team Scopus Importer:2024-12-16

Frequency preserving coherent opto-acoustic storage - Stiller, Birgit; Merklein, Moritz; Poulton, Christopher; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2018)
We experimentally demonstrate that the coherence of Brillouin-based storage is not affected by simultaneous storage on another frequency channel because of the accumulated phase mismatch over the length of the spatially extended acoustic phonon.
CRIS-Team Scopus Importer:2021-06-29

Frequency-selective excitation of guided acoustic modes in a photonic crystal fiber - Stiller, Birgit; Delque, M.; Beugnot, J. -C.; Lee, M. W.; Melin, G.; Maillotte, H.; Laude, Vincent; Sylvestre, Thibaut (Optics Express, 2011)
We present experimental and numerical results demonstrating the simultaneous frequency-selective excitation of several guided acoustic Brillouin modes in a photonic crystal fiber with a multi-scale structure design. These guided acoustic modes are identified by using a full vector finite-element model to result from elastic radial vibrations confined by the wavelength-scale air-silica microstructure. We further show the strong impact of structural irregularities of the fiber on the frequency and modal shape of these acoustic resonances. © 2011 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29

GHz kinematic sensing with classically entangled beams of light - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, M.; Giacobino, E.; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optics InfoBase Conference Papers, 2015)
CRIS-Team Scopus Importer:2021-06-29

Guided acousticwave brillouin scattering in a nanostructure core fiber - Beugnot, Jean Charles; Delqué, Michaël; Stiller, Birgit; Lee, Min Won; Maillotte, Hervé; Laude, Vincent; Mélin, Gilles; Sylvestre, Thibaut (Optics InfoBase Conference Papers, 2010)
We study guided acoustic wave Brillouin scattering in a nanostructure core fiber. Such design is shown, experimentally and numerically, to allow for the trapping of several acoustical modes overlapping efficiently with the optical one. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29

Guided Brillouin interactions - from optical vortex isolators to extreme thermodynamics - Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Brillouin-Mandelstam scattering is the strongest optomechanical effect in waveguides and optical fibers. It gives access to the domain of acoustic waves which follow other guiding rules and are sensitive to different parameters of the material such as pressure or temperature. This opens the opportunity to - on the one hand - modulate and process optical signals via mechanical vibrations which can be shaped by the design and material of the optoacoustic waveguides and - on the other hand - gain an insight into material properties and environmental changes. In this talk, experimental results on two topics will be presented.
CRIS-Team Scopus Importer:2024-12-16

Guided nonlinear optics for information processing - Brunner, Daniel; Stiller, Birgit; Psaltis, Demetri (Nanophotonics, 2025)
CRIS-Team Scopus Importer:2025-11-07

Highly localized distributed Brillouin scattering response in a photonic integrated circuit - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Li, Neuton; Vu, Khu; Choi, Duk-Yong; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (APL Photonics, 2018)
The interaction of optical and acoustic waves via stimulated Brillouin scattering (SBS) has recently reached on-chip platforms, which has opened new fields of applications ranging from integrated microwave photonics and on-chip narrow-linewidth lasers, to phonon-based optical delay and signal processing schemes. Since SBS is an effect that scales exponentially with interaction length, on-chip implementation on a short length scale is challenging, requiring carefully designed waveguides with optimized opto-acoustic overlap. In this work, we use the principle of Brillouin optical correlation domain analysis to locally measure the SBS spectrum with high spatial resolution of 800 μm and perform a distributed measurement of the Brillouin spectrum along a spiral waveguide in a photonic integrated circuit. This approach gives access to local opto-acoustic properties of the waveguides, including the Brillouin frequency shift and linewidth, essential information for the further development of high quality photonic-phononic waveguides for SBS applications.
CRIS-Team Scopus Importer:2021-06-29

High resolution brillouin sensing of micro-scale structures - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Eggleton, Benjamin J. (Applied Sciences, 2018)
Brillouin distributed measurement techniques have been extensively developed for structural health monitoring using fibre optic nerve systems. The recent advancement in the spatial resolution capabilities of correlation-based Brillouin distributed technique have reached the sub-mm regime, making this approach a suitable candidate for monitoring and characterizing integrated photonic devices. The small dimension associated with the short length of these devices-on the order of the cm- and mm-scale-requires high sensitivity detection techniques and sub-mm spatial resolution. In this paper, we provide an overview of the different Brillouin sensing techniques in various micro-scale structures such as photonic crystal fibres, microfibres, and on-chip waveguides. We show how Brillouin sensing is capable of detecting fine transverse geometrical features with the sensitivity of a few nm and also extremely small longitudinal features on the order of a few hundreds of μm. We focus on the technique of Brillouin optical correlation domain analysis (BOCDA), which enables such high spatial resolution for mapping the opto-acoustic responses of micro-scale waveguides.
CRIS-Team Scopus Importer:2021-06-29
Keywords: BOCDA; Distributed sensing; Photonic waveguides; Stimulated Brillouin scattering

High-Speed Coherent Photonic Random-Access Memory in Long-Lasting Sound Waves - Geilen, Andreas; Becker, Steven; Stiller, Birgit (ACS Photonics, 2024)
In recent years, remarkable advances in photonic computing have highlighted the need for photonic memory, particularly high-speed and coherent random-access memory. Addressing the ongoing challenge of implementing photonic memories is required to fully harness the potential of photonic computing. A photonic-phononic memory based on stimulated Brillouin scattering is a possible solution, as it coherently transfers optical information into sound waves at high-speed. Such an optoacoustic memory has shown great potential as it fulfills key requirements for high-performance optical random-access memory due to its coherence, on-chip compatibility, frequency selectivity, and high bandwidth. However, the storage time has so far been limited to a few nanoseconds due to the nanosecond decay of the acoustic wave. In this work, we experimentally enhance the intrinsic storage time of an optoacoustic memory by more than 1 order of magnitude and coherently retrieve optical information after a storage time of 123 ns. This is achieved by employing the optoacoustic memory in a highly nonlinear fiber at 4.2 K, increasing the intrinsic phonon lifetime by a factor of 6. We demonstrate the capability of our scheme by measuring the initial and readout optical data pulses with a direct and double homodyne detection scheme. Finally, we analyze the dynamics of the optoacoustic memory at different cryogenic temperatures in the range of 4.2-20 K and compare the findings to continuous wave measurements. The extended storage time is beneficial not only for photonic computing but also for Brillouin applications that require long phonon lifetimes, such as optoacoustic filters, true-time delay networks, and synthesizers in microwave photonics.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Brillouin scattering; cryogenics; nonlinear optics; optical memory; photonic neuromorphic computing

Implementation of an optoacoustic activation function based on stimulated Brillouin scattering - Becker, Steven; Storp, Jakob; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Artificial neural networks (ANNs) have emerged as powerful tools, which for example accelerate research on COVID-19. They solve challenging tasks by taking advantage of their self-learning abilities and nonlinearity [1, 2]. However, the freedom gained through the complexity of ANNs leads to computational intense model training, eventually consuming a lot of energy [3]. One possible solution to overcome the current issues could be by transferring ANNs into the optical domain. For instance, Shen et al. have demonstrated the rich capabilities of optical neural networks (ONNs) [4]. A key element of an ANN and ONN is its nonlinear activation function, however, only a few all-optical approaches are published. In addition, those published are frequency insensitive, limiting the maximum data bandwidth throughput.
CRIS-Team Scopus Importer:2024-12-16

Inter-vortex forward Brillouin scattering by chiral flexural phonons in twisted photonic crystal fibre - Zeng, Xinglin; Russell, Philip St. J.; Geilen, Andreas; Becker, Steven; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
We report forward stimulated Brillouin scattering between orthogonal circularly polarized vortex modes in chiral photonic crystal fibre. The interaction is mediated by cork-screw-like flexural phonons, which provide both linear and orbital angular momentum.
CRIS-Team Scopus Importer:2023-11-24

Inter-vortex forward Brillouin scattering by chiral phonons - Zeng, Xinglin; Russell, Philip St J.; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Forward Brillouin scattering (FBS) in optical fibres, in which co-propagating optical modes are coupled by acoustic modes, provides a powerful and flexible mechanism for controlling the structure and frequency of light fields, with applications in, e.g., high harmonic mode-locked fibre lasers [1] and optical sensing [2]. Here we report the observation of seeded inter-vortex Brillouin scattering in a three-fold rotationally symmetric photonic crystal fibre (PCF) [3], mediated by a rotating higher order flexural acoustic mode, sometimes known as a "screw mode" [4].
CRIS-Team Scopus Importer:2024-12-16

Localized high resolution brillouin spectrum measurement of a photonic integrated circuit - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Localized temperature and pressure measurements inside CS2-filled fiber using stimulated Brillouin scattering - Popp, Alexandra; Geilen, Andreas; Walter, Daniel; Chemnitz, Mario; Junaid, Saher; Poulton, Christopher G.; Marquardt, Christoph; Schmidt, Markus A.; Stiller, Birgit (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Liquid-core fibers are a versatile platform for nonlinear light-matter interactions, combining highly nonlinear materials like carbon disulfide (CS 2 ) or nitrobenzene with the confinement and long interaction length of optical fibers. While there is only minor influence of strain inside the fiber core due to the liquid phase, pressure effects have a dominant role depending on the thermodynamic regime and filling of the fiber core [1]. In our experiments we use Brillouin Optical Correlation Domain Analysis (BOCDA) to create a localized Brillouin response [2]. Due to the associated refractive index change, this response is strain, pressure and temperature dependent. While the discrimination of strain and temperature effects in silica fibers is complicated due to the combined Brillouin response [3] , CS 2 filled fibers have the advantage of thermo- and piezo-optical coefficients with different signs. While the thermo-optic coefficient is negative, resulting in a downshifted acoustic response for higher temperature, the piezo-optic coefficient is positive, resulting in an upshifted Brillouin frequency for increased pressure. To investigate the response of the CS 2 , we heated different parts of the 60cm liquid-core fiber on a hotplate up to a temperature of 135 C while measuring the distributed Brillouin response with a resolution of 4cm.
CRIS-Team Scopus Importer:2021-10-29

Localizing Eavesdroppers Inside a Quantum Channel Using Stimulated Brillouin Scattering - Popp, Alexandra; Stiller, Birgit; Marquardt, Christoph (2023 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC), 2023)
While modern communication systems pose a high standard of security using state-of-the-art encryption techniques based on computational hardness problems, quantum key distribution (QKD) offers a unique advantage using the laws of quantum mechanics. A secret key is shared between two parties, using quantum states of light over a quantum channel. Due to the quantum nature of the states, any interception or other way of eavesdropping will manifest in the distortion of the quantum state resulting in a change of accessible parameters. Whenever such a change of parameters is noticed, the shared key is marked unsecure and hashed down largely or, in the worst case, discarded.<br
Keywords: Quantum computing; Quantum channels; Europe; Quantum state; Distortion; Quantum key distribution; Encryption

Long-range and high-resolution distributed Brillouin fiber sensors Capteur Brillouin réparti à fibre optique à haute résolution et longue portée - Sylvestre, Thibaut; Lee, Min Won; Nguyen, Duc Minh; Stiller, Birgit; Beugnot, Jean Charles; Maillotte, Hervé; Hauden, Jérôme; Thévenaz, Luc (Instrumentation Mesure Metrologie, 2013)
Brillouin-based distributed optical fiber sensors have been the subject of intense research in recent years because they offer a unique solution for continuous, real-time monitoring in civil engineering and petroleum industry. These sensors provide strain or temperature measurements with meter spatial resolution over several tens of kilometers. In this work we demonstrate two new Brillouin fiber sensors with enhanced performances based on advanced modulation formats from high-speed lightwave communications systems. We first report a Brillouin distributed sensor with enhanced centimeter resolution using a digital phase-shift keying technique. The second one uses a quadrature phase-shift keying modulator as a single-sideband modulator to balance the pump depletion and the fiber loss by the Brillouin gain. Combined with a specially-designed in-line bidirectional Erbium-doped fiber amplifier, we demonstrate that this technique allows for the achievement of long-range distributed sensing over 100 km. © 2013 Lavoisier.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin optical time domain analysis; Distributed fiber sensors

Nonlinear single sideband microwave to optical conversion using an electro-optic WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2016)
Nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band is achieved within a crystalline whispering gallery mode resonator, reaching 0.1% photon number conversion efficiency with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Non-Reciprocal Delay Based on Photon-Phonon Interactions on a Chip - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (2019 Conference on Lasers and Electro-Optics, CLEO 2019 - Proceedings, 2019)
We demonstrate a non-reciprocal delay scheme based on stimulated Brillouin scattering in a planar highly nonlinear waveguide. The bandwidth of this scheme approaches a GHz, has wide frequency tunability and scales linearly with data power.
CRIS-Team Scopus Importer:2021-06-29

Nonreciprocal light-driven vortex isolator - Zeng, Xinglin; Russell, Philip St. J.; Frosz, Michael H.; Wong, Gordon Kwan Leung; Stiller, Birgit (Optics InfoBase Conference Papers, 2022)
We report a nonreciprocal reconfigurable light-driven isolator for vortex modes based on topology-selective Brillouin scattering in chiral PCF. The isolation rates are higher than 22 dB and 23 dB for 1st- and 2nd-order optical vortices.
CRIS-Team Scopus Importer:2022-09-09

Nonreciprocal vortex conversion and frequency shifting using light-driven chiral flexural waves - Zeng, Xinglin; Russell, Philip St. J.; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
We report nonreciprocal vortex conversion and frequency shifting via cork-screw-like chiral flexural phonons induced by forward Brillouin scattering in chiral photonic crystal fibre. A nonreciprocity factor greater than >13 dB is achieved.
CRIS-Team Scopus Importer:2023-11-24

Nonreciprocal vortex isolator via topology-selective stimulated Brillouin scattering - Zeng, Xinglin; Russell, Philip St. J.; Wolff, Christian; Frosz, Michael H.; Wong, Gordon Kwan Leung; Stiller, Birgit (Science Advances, 2022)
Optical nonreciprocity, which breaks the symmetry between forward and backward propagating optical waves, has become vital in photonic systems and enables many key applications. So far, all the existing nonreciprocal systems are implemented for linearly or randomly polarized fundamental modes. Optical vortex modes, with wavefronts that spiral around the central axis of propagation, have been extensively studied over the past decades and offer an additional degree of freedom useful in many applications. Here, we report a light-driven nonreciprocal isolation system for optical vortex modes based on topology-selective stimulated Brillouin scattering (SBS) in chiral photonic crystal fiber. The device can be reconfigured as an amplifier or an isolator by adjusting the frequency of the control signal. The experimental results show vortex isolation of 22 decibels (dB), which is at the state of the art in fundamental mode isolators using SBS. This device may find applications in optical communications, fiber lasers, quantum information processing, and optical tweezers.
CRIS-Team Scopus Importer:2022-11-04

Observation of acoustically induced modulation instability in a Brillouin photonic crystal fiber laser - Stiller, Birgit; Sylvestre, Thibaut (Optics Letters, 2013)
We report the experimental observation of self-induced modulation instability (MI) in a Brillouin fiber laser made with a solid-core photonic crystal fiber (PCF) with strong anomalous dispersion. We identify this MI as the result of parametric amplification of optical sidebands generated by guided acoustic modes within the core of the PCF. It is further shown that MI leads to passive harmonic mode locking and to the generation of a picosecond pulse train at a repetition rate of 1.15 GHz which matches the acoustic frequency of the fundamental acoustic mode of the PCF. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29

Observation of Brillouin linewidth broadening and decay time in photonic crystal fiber - Stiller, Birgit; Beugnot, J. C.; Foaleng Mafang, S.; Lee, M. W.; Delqué, M.; Kudlinski, A.; Maillotte, H.; Laude, V.; Thévenaz, L.; Sylvestre, T. (2010 IEEE Photonics Society Summer Topical Meeting Series, PHOSST 2010, 2010)
We present a novel distributed sensing technique that allows for the observation of Brillouin gain spectral distribution and acoustic decay time in photonic crystal fiber as well as in standard single-mode fiber. © 2010 IEEE.
CRIS-Team Scopus Importer:2021-06-29

On-chip broadband nonreciprocal light storage - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (Nanophotonics, 2021)
Breaking the symmetry between forward- and backward-propagating optical modes is of fundamental scientific interest and enables crucial functionalities, such as isolators, circulators, and duplex communication systems. Although there has been progress in achieving optical isolation on-chip, integrated broadband nonreciprocal signal processing functionalities that enable transmitting and receiving via the same low-loss planar waveguide, without altering the frequency or mode of the signal, remain elusive. Here, we demonstrate a nonreciprocal delay scheme based on the unidirectional transfer of optical data pulses to acoustic waves in a chip-based integration platform. We experimentally demonstrate that this scheme is not impacted by simultaneously counterpropagating optical signals. Furthermore, we achieve a bandwidth more than an order of magnitude broader than the intrinsic optoacoustic linewidth, linear operation for a wide range of signal powers, and importantly, show that this scheme is wavelength preserving and avoids complicated multimode structures.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin scattering; integrated photonics; nonreciprocity; optical delay

On-chip coherent photonic-phononic memory - Stiller, Birgit; Merklein, Moritz; Eggleton, Benjamin J. (Proceedings - International Conference Laser Optics 2018, ICLO 2018, 2018)
We store optical data in acoustic waves on a planar waveguide based on stimulated Brillouin scattering (SBS) and demonstrate multiple conversions of information between the optical and acoustic domain. We show the coherent acousto-optic transfer by retrieving multiple amplitude and phase levels with GHz bandwidth and demonstrate multi-wavelength operation.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Nonlinear optics; Photonic integrated circuits; Stimulated Brillouin scattering

On-chip correlation-based Brillouin sensing: Design, experiment, and simulation - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Liu, Yang; Morrison, Blair; Casas-Bedoya, Alvaro; Ren, Guanghui; Nguyen, Thach G.; Vu, Khu; Choi, Duk-Yong; Mitchell, Arnan; Madden, Steven J.; et al. (Journal of the Optical Society of America B-Optical Physics, 2019)
Wavelength-scale stimulated Brillouin scattering (SBS) waveguides are enabling novel on-chip functionalities. The microscale and nanoscale SBS structures and the complexity of the SBS waveguides require a characterization technique to monitor the local geometry-dependent SBS responses along the waveguide. In this work, we demonstrate an experimental spatial resolution of 500 μm, which can detect feature sizes down to 200 μm on a silicon–chalcogenide photonic waveguide using the Brillouin optical correlation domain analysis technique. We provide extensive simulation and analysis of how multiple acoustic and optical modes associated with geometrical variations influence the Brillouin spectrum.
CRIS-Team Scopus Importer:2021-06-29

On-chip multi-stage optical delay based on cascaded Brillouin light storage - Stiller, Birgit; Merklein, Moritz; Wolff, Christian; Vu, Khu; Ma, Pan; Poulton, Christopher G.; Madden, Stephen J.; Eggleton, Benjamin J. (Optics Letters, 2018)
Storing and delaying optical signals plays a crucial role in data centers, phased array antennas, communication, and future computing architectures. Here, we show a delay scheme based on cascaded Brillouin light storage that achieves multi-stage delay at arbitrary positions within a photonic integrated circuit. Importantly these multiple resonant transfers between the optical and acoustic domain are controlled solely via external optical control pulses, allowing cascading of the delay without the need of aligning multiple structural resonances along the optical circuit.
CRIS-Team Scopus Importer:2021-06-29

On-chip non-reciprocal light storage - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Optically replenishing coherent acoustic phonons in photonic circuits - Merklein, M.; Stiller, Birgit; Wolff, C.; Vu, K.; Madden, S. J.; Eggleton, B. J. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Optical Vortex Brillouin Laser - Zeng, Xinglin; Russell, Philip St. J.; Chen, Yang; Wang, Zheqi; Wong, Gordon Kwan Leung; Roth, Paul; Frosz, Michael H.; Stiller, Birgit (Laser & Photonics Reviews, 2023)
Optical vortices, which have been extensively studied over the last decades, offer an additional degree of freedom useful in many applications, such as optical tweezers and quantum control. Stimulated Brillouin scattering (SBS), providing a narrow linewidth and a strong nonlinear response, has been used to realize quasi-continuous wave lasers. Here, stable oscillation of optical vortices and acoustic modes in a Brillouin laser based on chiral photonic crystal fiber (PCF) is reported, which robustly supports helical Bloch modes (HBMs) that carry circularly polarized optical vortex and display circular birefringence. A narrow-linewidth Brillouin fiber laser that stably emits 1st- and 2nd-order vortex-carrying HBMs is implemented. Angular momentum conservation selection rules dictate that pump and backward Brillouin signals have opposite topological charge and spin. Additionally, it is shown that when the chiral PCF is placed within a laser ring cavity, the linewidth-narrowing associated with lasing permits the peak of the Brillouin gain that corresponds to acoustic mode to be measured with resolution of 10 kHz and accuracy of 520 kHz. The results pave the way to a new generation of vortex-carrying SBS systems with applications in optical tweezers, quantum information processing, and vortex-carrying nonreciprocal systems.
CRIS-Team Scopus Importer:2023-02-17
Keywords: chiral optics; optical vortices; photonic crystal fibers; stimulated Brillouin scattering

Optoacoustic active cooling in waveguides - Martínez, Laura Blázquez; Wiedemann, Philipp; Geilen, Andreas; Zhu, Changlong; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Brillouin-Mandelstam scattering, the interaction of two photons mediated by an acoustic phonon, is one of the strongest third order nonlinearities in optical fibers. In contrast to optomechanical cavities, where Stokes and anti-Stokes processes interact with the same mechanical phonon, the acoustic phonons addressed in a backward Brillouin scattering process are different for Stokes and anti-Stokes processes. Therefore, in order to achieve phonon cooling, there is no need to work in the resolved sideband regime [1].
CRIS-Team Scopus Importer:2024-12-16

Optoacoustic Building Blocks for Photonic Neural Networks - Cabello, Jesús Humberto Marines; Slinkov, Grigorii; Saffer, Olivia; Braband, Niklas; Geilen, Andreas; Becker, Steven; Stiller, Birgit (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
The realization of massive machine learning models has integrated artificial intelligence into our daily lives, yet, their training, maintenance, and scalability rely on power-hungry electronic processors [1]. Neuromorphic computing seeks to address these challenges by mimicking neural architechtures directly in physical systems. Photonics is a promising platform as it offers high bandwidth, rapid processing speeds, and low energy consumption [2, 3]. Examples showing the potential of photonics include reservoir computing and extreme learning machines using optical components [4], deep diffractive neural networks [5], and Mach-Zender interferometer meshes [6].
CRIS-Team Scopus Importer:2025-09-26

Optoacoustic Cooling of Traveling Hypersound Waves - Blázquez Martínez, Laura; Wiedemann, Philipp; Zhu, Changlong; Geilen, Andreas; Stiller, Birgit (Physical Review Letters, 2024)
We experimentally demonstrate optoacoustic cooling via stimulated Brillouin-Mandelstam scattering in a 50 cm long tapered photonic crystal fiber. For a 7.38 GHz acoustic mode, a cooling rate of 219 K from room temperature has been achieved. As anti-Stokes and Stokes Brillouin processes naturally break the symmetry of phonon cooling and heating, resolved sideband schemes are not necessary. The experiments pave the way to explore the classical to quantum transition for macroscopic objects and could enable new quantum technologies in terms of storage and repeater schemes.
CRIS-Team Scopus Importer:2024-01-26

Opto-acoustic coupling and Brillouin phenomena in microstructure optical fibers - Maillotte, Hervé; Beugnot, Jean Charles; Stiller, Birgit; Lee, Min Won; Nguyen, Duc Minh; Delqué, Michael; Benchabane, Sarah; Laude, Vincent; Mafang, Stella Foaleng; Thévenaz, Luc; Bouwmans, Géraud; Kudlinski, Alexandre; et al. (Technical Digest - 2012 17th Opto-Electronics and Communications Conference, OECC 2012, 2012)
Like photonic crystals have revolutionized the way of manipulating optical waves at the sub-micron scale, phononic crystals have more recently played similar decisive role for sound waves, or more generally elastic waves. Then, the idea of coupling light and sound in purposely designed microstructures is now emerging. In this respect, the periodic, wavelength-scale (for both optic and high-frequency acoustic waves) transverse air-hole microstructure of photonic crystal fibers (PCFs) provides additional degrees of freedom for light-sound interactions. PCFs can indeed exhibit photonic and phononic bandgap effects, allowing for tight confinement and joint waveguiding of both types of waves [1]. Electrostriction-driven Brillouin phenomena, namely backward Stimulated Brillouin Scattering (SBS) and forward Guided Acoustic Wave Brillouin Scattering (GAWBS), constitute an important category of such opto-acoustic coupling. The geometry of PCFs can dramatically modify the Brillouin spectrum, the gain and the stimulated Brillouin threshold, globally yielding much richer opto-acoustic dynamics and spectral features than in conventional fibers [2-11]. Specific transverse or longitudinal guided acoustics modes in the 100 MHz-10 GHz range can thus be selectively excited, resonantly enhanced and tightly confined within the microstructure, with an intimate dependence on its μm or sub-μm geometry. All these specific features have great potential for developing novel PCF-based distributed Brillouin sensors [6,7,12-14], for high-resolution longitudinal mapping of the intrinsic fluctuations of the fiber microstructure [15], and more generally for developing original tools of optical signal processing [1-4,9,16,17]. This talk will give a comprehensive overview of these original behaviors in a range of PCFs. © 2012 IEEE.
CRIS-Team Scopus Importer:2021-06-29

Optoacoustic Entanglement in a Continuous Brillouin-Active Solid State System - Zhu, Changlong; Genes, Claudiu; Stiller, Birgit (Physical Review Letters, 2024)
Entanglement in hybrid quantum systems comprised of fundamentally different degrees of freedom, such as light and mechanics, is of interest for a wide range of applications in quantum technologies. Here, we propose to engineer bipartite entanglement between traveling acoustic phonons in a Brillouin active solid state system and the accompanying light wave. The effect is achieved by applying optical pump pulses to state-of-the-art waveguides, exciting a Brillouin Stokes process. This pulsed approach, in a system operating in a regime orthogonal to standard optomechanical setups, allows for the generation of entangled photon-phonon pairs, resilient to thermal fluctuations. We propose an experimental platform where readout of the optoacoustics entanglement is done by the simultaneous detection of Stokes and anti-Stokes photons in a two-pump configuration. The proposed mechanism presents an important feature in that it does not require initial preparation of the quantum ground state of the phonon mode.
CRIS-Team Scopus Importer:2024-11-29

Optoacoustic entanglement in Brillouin-active waveguides - Zhu, Changlong; Genes, Claudiu; Stiller, Birgit (Quantum 2.0 in Proceedings Quantum 2.0 Conference and Exhibition, 2024)
Entanglement is a key resource to many emerging quantum technologies. Here, we present a scheme to engineer bipartite entanglement between traveling acoustic phonons and photons in Brillouin-active waveguides at a modest high environment temperature.
CRIS-Team Scopus Importer:2025-02-04

Optoacoustics-Advances in high-frequency optomechanics and Brillouin scattering - Stiller, Birgit; Dainese, Paulo; Verhagen, Ewold (APL Photonics, 2019)
The fields of cavity optomechanics and Brillouin scattering, linked by common underlying physical mechanisms, involve the interaction of light waves with mechanical vibrations at the micro- A nd nanoscale. Exciting fundamental research in both classical and quantum regimes as well as opportunities for applications in microwave photonics, frequency conversion, narrow-linewidth lasers, optomechanical sensors, electro-optic transducers, coherent light storage, and Brillouin spectroscopy have stimulated significant interest in the last decade. This special issue brings contributions to fundamental aspects regarding the Brillouin interaction such as novel waveguide structures, novel guiding mechanisms, the interplay between Brillouin and other nonlinear phenomena, and applications in sensing and light storage, as well as an introductory tutorial to the research field. Here, we provide a brief introduction to the topics covered in the issue.
CRIS-Team Scopus Importer:2021-06-29

Opto-electronic oscillator employing photonic-chip based stimulated Brillouin scattering - Merklein, Moritz; Stiller, Birgit; Kabakova, Irina V.; Mutugala, Udara S.; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J.; Slavík, Radan (Optics InfoBase Conference Papers, 2016)
We demonstrate an optoelectronic oscillator based on stimulated Brillouin scattering as an active filter on a photonic chip. An ultrahigh Brillouin gain chalcogenide rib waveguide is used to generate low-noise single-mode 10 GHz RF signals.
CRIS-Team Scopus Importer:2021-06-29

Order of Magnitude Increase in Storage Time of Photonic-Phononic Memory - Becker, Steven; Geilen, Andreas; Stiller, Birgit (2023 International Conference on Photonics in Switching and Computing, PSC 2023, 2023)
With the recent developments in photonic computing platforms, the need of novel optical memories becomes increasingly important. Optoacoustic memories have shown great potential due to their quick access time, coherent nature, and broad bandwidth. These continuously tunable memories can be controlled entirely optically, but so far their intrinsic storage time is limited by the acoustic life time to approximately 10 ns. In this work, we experimentally demonstrate a cryogenic optoacoustic memory with an intrinsic storage time beyond 135 ns.
CRIS-Team Scopus Importer:2023-12-15
Keywords: nonlinear optics; Optical computing; optical memory; stimulated Brillouin scattering

Phase regeneration of a star-8QAM signal in a phase-sensitive amplifier with conjugated pumps - Stiller, Birgit; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2014)
We demonstrate numerically phase regeneration of a star-8QAM signal with two amplitude and four phase states in a phase-sensitive amplifier. In a dual-stage setup, two phase-conjugated idlers are generated in a first stage consisting of two fiber-optic parametric phase-insensitive amplifiers operated in highly nonlinear gain regime. These are used as pumps in the second, phase-sensitive amplification stage which enables efficient phase regeneration via a degenerate four-wave-mixing process. The latter can be operated in two different operation modes: without format conversion or with phase-shifted amplitude levels. In both regimes, we observe high phase-regeneration efficiency for all amplitude levels: the initial phase noise with 0.2 rad standard deviation is reduced by a factor of 5.
lhft_intern.bib::Stiller2014

Photonic Activation Function Using Sound Waves - Slinkov, Grigorii; Becker, Steven; Englund, Dirk; Stiller, Birgit (2023 International Conference on Photonics in Switching and Computing, PSC 2023, 2023)
We experimentally demonstrate an in-fiber optoacoustic nonlinear activation function based on stimulated Brillouin scattering. The activation function can be tuned all-optically and shows an input-output behaviour of a LeakyReLU, Sigmoid, and quadratic function. Our scheme is coherent and frequency selective, which is suitable for operation in multi-frequency neural networks. In addition, the optoacoustic activation function can amplify its input signal, allowing to compensate on-the-fly for optical losses during propagation.
CRIS-Team Scopus Importer:2023-12-15
Keywords: neuromorphic computing; nonlinear optics; Optical neural networks; stimulated Brillouin scattering

Photonic-chip based widely tunable microwave source using a Brillouin opto-electronic oscillator - Merklein, Moritz; Stiller, Birgit; Kabakova, Irina V.; Mutugala, Udara S.; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J.; Slavík, Radan (Optics InfoBase Conference Papers, 2016)
We demonstrate the first widely tunable chip-based opto-electronic microwave source based on stimulated Brillouin scattering. The output frequency can be tuned over 40 GHz and the phase-noise performance is comparable to high-range laboratory RF sources.
CRIS-Team Scopus Importer:2021-06-29

Photonic crystal fiber mapping using Brillouin echoes distributed sensing - Stiller, Birgit; Foaleng, S. M.; Beugnot, J. -C.; Lee, M. W.; Delque, M.; Bouwmans, Geraud; Kudlinski, Alexandre; Thevenaz, Luc; Maillotte, H.; Sylvestre, Thibaut (Optics Express, 2010)
In this paper we investigate the effect of microstructure irregularities and applied strain on backward Brillouin scattering by comparing two photonic crystal fibers drawn with different parameters in order to minimize diameter and microstructure fluctuations. We fully characterize their Brillouin properties including the gain spectrum and the critical power. Using Brillouin echoes distributed sensing with a high spatial resolution of 30 cm we are able to map the Brillouin frequency shift along the fiber and get an accurate estimation of the microstructure longitudinal fluctuations. Our results reveal a clear-cut difference of longitudinal homogeneity between the two fibers. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29

Picosecond acoustic dynamics in stimulated Brillouin scattering - Piotrowski, Johannes; Schmidt, Mikolaj K.; Stiller, Birgit; Poulton, Christopher G.; Steel, Michael J. (Optics Letters, 2021)
Recent experiments demonstrating storage of optical pulses in acoustic phonons via stimulated Brillouin scattering raise questions about the spectral and temporal capacities of such protocols and the limitations of the theoretical frameworks routinely used to describe them. We consider the dynamics of photon-phonon scattering induced by optical pulses with temporal widths comparable to the period of acoustic oscillations. We revisit the widely adopted classical formalism of coupled modes and demonstrate its breakdown. We use a simple extension to the formulation and find potentially measurable consequences in the dynamics of Brillouin experiments involving ultrashort pulses.
CRIS-Team Scopus Importer:2021-06-25

Quantum coherent control in pulsed waveguide optomechanics - Zhang, Junyin; Zhu, Changlong; Wolff, Christian; Stiller, Birgit (Physical Review Research, 2023)
Coherent control of traveling acoustic excitations in a waveguide system is an interesting way to manipulate and transduce classical and quantum information. So far, these interactions, often based on optomechanical resonators or Brillouin scattering, have been studied in the steady-state regime using continuous waves. However, waveguide experiments are often based on optical pump pulses, which require treatment in a dynamic framework. In this paper, we present an effective Hamiltonian formalism in the dynamic regime using optical pulses that links waveguide optomechanics and cavity optomechanics, which can be used in the classical and quantum regime including quantum noise. Based on our formalism, a closed solution for coupled-mode equation under the undepleted assumption is provided and we found that the strong coupling regime is already accessible in current Brillouin waveguides by using pulses. We further investigate several possible experiments within waveguide optomechanics, including Brillouin-based coherent transfer, Brillouin cooling, and optoacoustic entanglement.
CRIS-Team Scopus Importer:2023-02-24

Quantum coherent control in pulsed waveguide optomechanics for photon-phonon entanglement via Brillouin scattering - Zhu, Changlong; Zhang, Junyin; Wolff, Christian; Stiller, Birgit (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Brillouin optomechanics provides a way to coherently control traveling acoustic excitations in waveguides system, which enables the manipulation and processing of classical and quantum information. Although Brillouin optomechanics has been largely investigated in the steady-state regime using continuous waves [1-3], waveguide experiments are often realized by using optical pulses for example for Brillouin-based memory [4,5]. This requires a dynamic framework treatment for the temporal domain including the noise dynamics.
CRIS-Team Scopus Importer:2024-12-16

Quantum hacking of continuous-variable quantum key distribution systems: Realtime Trojan-horse attacks - Stiller, Birgit; Khan, Imran; Jain, Nitin; Jouguet, P.; Kunz-Jacques, S.; Diamanti, E.; Marquardt, Christoph; Leuchs, Gerd (Conference on Lasers and Electro-Optics Europe - Technical Digest, 2015)
We experimentally demonstrate successful Trojan-horse attacks on laboratory and commercial continuous-variable quantum key distribution systems with binary and Gaussian modulation. Furthermore, we analyze appropriate countermeasures regarding their spectral performance.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Optical pulses; Optical refraction; Optical variables control; Phase modulation; Protocols; Security

Quantum-limited measurements of optical signals from a geostationary satellite - Günthner, Kevin; Khan, Imran; Elser, Dominique Alexander; Stiller, Birgit; Bayraktar, Ömer; Mueller, Christian R.; Saucke, Karen; Troendle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optica, 2017)
The measurement of quantum signals that travel through long distances is fundamentally and technologically interesting. We present quantum-limited coherent measurements of optical signals that are sent from a satellite in geostationary Earth orbit to an optical ground station. We bound the excess noise that the quantum states could have acquired after having propagated 38,600 km through Earth’s gravitational potential, as well as its turbulent atmosphere. Our results indicate that quantum communication is feasible, in principle, in such a scenario, highlighting the possibility of a global quantum key distribution network for secure communication.
CRIS-Team Scopus Importer:2021-06-29
Keywords: (010.1300) Atmospheric propagation; (060.1660) Coherent communications; (060.2605) Free-space optical communication; (270.5565) Quantum communications; (270.5568) Quantum cryptography

Quantum-limited measurements of optical signals from a satellite in geostationary earth orbit - Günthner, Kevin; Khan, Imran; Elser, Dominique; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Quantum-limited measurements of signals from geostationary earth orbit - Elser, Dominique; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (European Conference on Optical Communication, ECOC, 2016)
Quantum key distribution (QKD) has been implemented in metropolitan area networks around the world. Optical satellite communication is seen as suitable to provide the missing long-haul interconnections. We validate this approach by quantum measurements of optical signals from space.
CRIS-Team Scopus Importer:2021-06-29

Quantum measurements of signals from the Alphasat TDP1 laser communication terminal - Elser, D.; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, K.; Tröndle, D.; Heine, F.; Seel, S.; Greulich, P.; Zech, H.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Quantum optics [1] can be harnessed to implement cryptographic protocols that are verifiably immune against any conceivable attack [2]. Even quantum computers, that will break most current public keys [3, 4], cannot harm quantum encryption. Based on these intriguing quantum features, metropolitan quantum networks have been implemented around the world [5-15]. However, the long-haul link between metropolitan networks is currently missing [16]. Existing fiber infrastructure is not suitable for this purpose since classical telecom repeaters cannot relay quantum states [2]. Therefore, optical satellite-to-ground communication [17-22] lends itself to bridge intercontinental distances for quantum communication [23-40].
CRIS-Team Scopus Importer:2021-06-29

Quantum memory in Brillouin-active waveguides - Zhu, Changlong; Stiller, Birgit (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
Storage and retrieval of optical quantum states are key elements for the realization of quantum communication and quantum networks. Here, we propose to realize a memory for light states in Brillouin-active waveguides. It is achieved by transferring quantum states between optical photons and acoustic phonons via Brillouin anti-Stokes scattering. By controlling the optoacoustic interaction with pulsed pumps, we demonstrate that it is possible to write, store, and read out of optical quantum states with high fidelity in state-of-the-art Brillouin-active waveguides.
CRIS-Team Scopus Importer:2025-09-26

Refreshed opto-acoustic memory - Stiller, Birgit; Merklein, Moritz; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Storing and delaying optical information is of crucial importance for optical communications, signal processing and in the quantum domain. A plethora of techniques for optical storage have been shown which aim to maintain as much as possible the advantages of optics, such as e.g. the coherence, the bandwidth and capacity. In particular the interaction of optical waves with mechanical motion offers a solution to buffer optical information [1-4]. It was shown that one can use acoustic waves to store and delay optical signals coherently via the effect of stimulated Brillouin scattering (SBS) [3,4]. This allows for simultaneous storage at multiple wavelengths [5], cascaded storage at different spatial positions [6], and nonreciprocal storage with a GHz bandwidth [7]. However, the delay time of this technique is so far limited to the acoustic lifetime of about 10 ns.
CRIS-Team Scopus Importer:2021-06-29

Risk analysis of Trojan-horse attacks on practical quantum key distribution systems - Jain, Nitin; Stiller, Birgit; Khan, Imran; Makarov, Vadim; Marquardt, Christoph; Leuchs, Gerd (IEEE Journal of Selected Topics in Quantum Electronics, 2015)
An eavesdropper Eve may probe a quantum key distribution (QKD) system by sending a bright pulse from the quantum channel into the system and analyzing the back-reflected pulses. Such Trojan-horse attacks can breach the security of the QKD system, if appropriate safeguards are not installed or if they can be fooled by the Eve. We present a risk analysis of such attacks based on extensive spectral measurements, such as transmittance, reflectivity, and detection sensitivity of some critical components used in a typical QKD systems. Our results indicate the existence of wavelength regimes, where the attacker gains considerable advantage as compared to launching an attack at 1550 nm. We also propose countermeasures to reduce the risk of such attacks.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Electrooptic modulators; Fiber optics; Infrared detectors; Infrared spectra; Optical pulses; Optical receivers; Photodetectors; Quantum cryptography; Quantum key distribution; Reflectometry; Supercontinuum; Transmittance; Trojan-horse attack

Satellite quantum communication via the alphasat laser communication terminal quantum signals from 36 thousand kilometers above earth - Elser, Dominique Alexander; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Marquardt, Christoph; Leuchs, Gerd; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (2015 IEEE International Conference on Space Optical Systems and Applications, ICSOS 2015, 2016)
By harnessing quantum effects, we nowadays can use encryption that is in principle proven to withstand any conceivable attack. These fascinating quantum features have been implemented in metropolitan quantum networks around the world. In order to interconnect such networks over long distances, optical satellite communication is the method of choice. Standard telecommunication components allow one to efficiently implement quantum communication by measuring field quadratures (continuous variables). This opens the possibility to adapt our Laser Communication Terminals (LCTs) to quantum key distribution (QKD). First satellite measurement campaigns are currently validating our approach.
CRIS-Team Scopus Importer:2021-06-29
Keywords: free-space optical communication; quantum cryptography; quantum key distribution; satellite quantum communication; satellite-ground laser communication

SBS mitigation in a microstructured optical fiber by periodically varying the core diameter - Stiller, Birgit; Kudlinski, Alexandre; Lee, Min Won; Bouwmans, Geraud; Delque, Michael; Beugnot, Jean-Charles; Maillotte, Herve; Sylvestre, Thibaut (IEEE Photonics Technology Letters, 2012)
In this letter, we experimentally demonstrate a 4-dB increase of the stimulated Brillouin scattering threshold in a microstructured optical fiber. This result is obtained by periodically varying the size of the air-hole structure by only 7% amplitude, while keeping a low attenuation coefficient. The efficiency of this passive technique is verified by use of the Brillouin echoes-distributed sensing technique where the Brillouin frequency-shift oscillation is clearly observed. © 1989-2012 IEEE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin threshold; distributed Brillouin measurement; microstructured optical fiber; stimulated Brillouin scattering

Sensitivity enhancement in long-range distributed Brillouin fiber sensor using an anti-Stokes single-sideband probe and a bidirectional EDFA - Nguyen, D. M.; Stiller, Birgit; Lee, M. W.; Beugnot, J. C.; Maillotte, H.; Sylvestre, T.; Mottet, A.; Hauden, J. (2012 Photonics Global Conference, PGC 2012, 2012)
We demonstrate a long-range Brillouin optical time-domain analysis (BOTDA) sensor system with a sensing range up to 100-km by combining an anti-Stokes single sideband suppressed-carrier modulation technique with an in line mid-span bidirectional EDFA. © 2012 IEEE.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin optical time domain analysis; EDFA; fiber optic sensor; single-sideband modulation

Short-Scale Photon-Phonon Interactions - Stiller, Birgit; Merklein, Moritz; Eggleton, Benjamin J. (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2018)
Using photon-phonon interactions, we experimentally demonstrate the storage of 200ps-long optical pulses for over 70 pulse widths. We moreover show that this concept is suitable for the non-reciprocal storage at multiple optical wavelengths.
CRIS-Team Scopus Importer:2021-06-29

Simultaneous opto-acoustic light storage at multiple frequency channels - Stiller, Birgit; Merklein, Moritz; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (2017 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2017, 2017)
We store optical data in acoustic waves on a planar waveguide based on stimulated Brillouin scattering (SBS) and demonstrate for the first time that this coherent light storage concept allows for the simultaneous storage at different frequency channels, separated by 100 GHz, without observable cross-talk between the individual channels.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Nonlinear optics; Photonic integrated circuits; Stimulated Brillouin scattering

Single sideband microwave to optical photon conversion-an electro-optic realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2017)
We present results on nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band with more than 0.1% photon number conversion efficiency with MHz bandwidth, in a crystalline whispering gallery mode resonator.
CRIS-Team Scopus Importer:2021-06-29

Spin-orbit interaction in nanofiber-based Brillouin scattering - Zerbib, Maxime; Romanet, Maxime; Sylvestre, Thibaut; Wolff, Christian; Stiller, Birgit; Beugnot, Jean Charles; Huy, Kien Phan (Optics Express, 2023)
Angular momentum is an important physical property that plays a key role in light-matter interactions, such as spin-orbit interaction. Here, we investigate theoretically and experimentally the spin-orbit interaction between a circularly polarized optical (spin) and a transverse vortex acoustic wave (orbital) using Brillouin backscattering in a silica optical nanofiber. We specifically explore the state of polarization of Brillouin backscattering induced by the TR21 torso-radial vortex acoustic mode that carries an orbital angular momentum. Using a full-vectorial theoretical model, we predict and observe two operating regimes for which the backscattered Brillouin signal is either depolarized or circularly polarized, depending on the input pump polarization. We demonstrate that when the pump is circularly polarized and thus carries a spin angular momentum, the backscattered signal undergoes a handedness reversal of circular polarization due to opto-acoustic spin-orbit interaction and the conservation of overall angular momentum.
CRIS-Team Scopus Importer:2023-07-21

Stimulated Brillouin scattering in chiral photonic crystal fiber - Zeng, Xinglin; He, Wenbin; Frosz, Michael H.; Geilen, Andreas; Roth, Paul; Wong, Gordon Kwan Leung; Russell, Philip St. J.; Stiller, Birgit (Photonics Research, 2022)
Stimulated Brillouin scattering (SBS) has many applications; for example, in sensing, microwave photonics, and signal processing. Here, we report the first experimental study of SBS in chiral photonic crystal fiber (PCF), which displays optical activity and robustly maintains circular polarization states against external perturbations. As a result, circularly polarized pump light is cleanly backscattered into a Stokes signal with the orthogonal circular polarization state, as is required by angular momentum conservation. By comparison, untwisted PCF generates a Stokes signal with an unpredictable polarization state, owing to its high sensitivity to external perturbations. We use chiral PCF to realize a circularly polarized continuous-wave Brillouin laser. The results pave the way for a new generation of stable circularly polarized SBS systems with applications in quantum manipulation, optical tweezers, optical gyroscopes, and fiber sensors. (C) 2022 Chinese Laser Press
CRIS-Team WoS Importer:2022-03-18

Storing light as sound in a photonic integrated circuit - Merklein, Moritz; Stiller, Birgit; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J. (Proceedings of Frontiers in Optics 2015, FIO 2015, 2015)
We demonstrate for the first time the storage of nanosecond light pulses as acoustic phonons in a photonic integrated circuit. The light pulses are subsequently retrieved, after being stored for several nanoseconds.
CRIS-Team Scopus Importer:2021-06-29

Strong optoacoustic interaction in hot CS2-filled liquid-core optical fiber - Geilen, Andreas; Popp, Alexandra; Walter, Daniel; Chemnitz, Mario; Junaid, Saher; Poulton, Christopher G.; Marquardt, Christoph; Schmidt, Markus A.; Stiller, Birgit (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Optical fibers with a liquid core provide a versatile platform for nonlinear optics [1]. Filled with carbon disulfide (CS 2 ), the high linear refractive index of 1.59 at 1549 nm and low speed of sound of 1250 ms -1 , compared to silica, ensures guidance of optical and acoustic waves inside the fiber core. This type of fiber also provides a large optoacoustic interaction via stimulated Brillouin scattering (SBS) [2] due to the high optical nonlinearity of CS 2 , as well as the long interaction length and the low optical loss.
CRIS-Team Scopus Importer:2021-10-29

Supercontinuum generation in the black light region by pumping at 355 nm a silica photonic crystal fiber - Sylvestre, Thibaut; Ragueh, A. R.; Lee, M. W.; Stiller, Birgit; Fanjoux, G.; Barviau, Benoit; Mussot, Arnaud; Kudlinski, Alexandre (Proceedings of SPIE - The International Society for Optical Engineering, 2012)
We have developed a fibre-based source of "black light", a source that emits broadband ultraviolet radiation but only small amounts of visible light and no infrared light. We made this source by pumping a specially designed silica photonic crystal fibre with 355 nm light pulses from a Q-switched frequency-tripled Nd:YAG laser. Four-wave mixing and cascaded Raman generation combine in the fibre to provide a broadband continuum output that spans from around 350 nm to 390-470 nm, with the exact spectral width dependent on the pump power. We discuss the main limitations in terms of bandwidth and power due to temporal walk-off, fiber attenuation and solarization and we suggest simple solutions for further progress. This broadband black-light source could be useful for performing gas absorption spectroscopy or exciting various fluorescent proteins used in biological studies. © 2012 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
CRIS-Team Scopus Importer:2021-06-29
Keywords: Four-wave mixing; Photonic crystal fibers; Stimulated Raman scattering; Supercontinuum generation

Supercontinuum generation with picosecond ultraviolet pulses in a solid-core photonic crystal fiber - Sylvestre, T.; Lee, M. W.; Ragueh, A. R.; Stiller, Birgit; Fanjoux, G.; Barviau, B.; Mussot, A.; Kudlinski, A. (Optics InfoBase Conference Papers, 2012)
Black light supercontinuum generation is demonstrated as a result of picosecond pumping a solid-core photonic crystal fiber at 355 nm through the combined effects of intermodal four-wave mixing and cascaded Raman scattering. © 2012 OSA.
CRIS-Team Scopus Importer:2021-06-29

Suppression of SBS in a photonic crystal fiber with periodically-varied core diameter - Stiller, Birgit; Lee, Min Won; Delqué, Michaël; Bouwmans, Géraud; Kudlinski, Alexandre; Beugnot, Jean Charles; Maillotte, Hervé; Sylvestre, Thibaut (Optics InfoBase Conference Papers, 2011)
We experimentally demonstrate 7 dB improvement in Brillouin suppression in a photonic crystal fiber by periodically varying the size of the air-hole-structure by only 7% amplitude while keeping a low attenuation coefficient. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29

Temperature coefficient of the high-frequency guided acoustic mode in a photonic crystal fiber - Carry, Emile; Beugnot, Jean-Charles; Stiller, Birgit; Lee, Min W.; Maillotte, Herve; Sylvestre, Thibaut (Applied Optics, 2011)
High-frequency guided acoustic Brillouin modes have recently been observed in small-core silica photonic crystal fibers. In this paper, we investigate the temperature dependence of the optical sideband frequency generated by one of these guided acoustic waves. The experimental results show a temperature coefficient of 100 kHz/°C at an acoustic resonance frequency of 1.15GHz and are in very good agreement with the theoretical predictions. This coefficient demonstrates a temperature sensitivity 10 times larger than that previously reported in conventional single-mode fibers, which is promising in view of potential applications to optical fiber sensors. © 2011 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29

Theory of cascaded forward brillouin scattering - Wolff, C.; Stiller, Birgit; Steel, M. J.; Eggleton, B. J.; Poulton, C. G. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Thermodynamic Control of Nanoliter Volumes of CS2 via Stimulated Brillouin Scattering - Geilen, Andreas; Popp, Alexandra; Das, Debayan; Junaid, Saher; Poulton, Christopher; Chemnitz, Mario; Marquardt, Christoph; Schmidt, M. A.; Stiller, Birgit (Optics InfoBase Conference Papers, 2022)
We present Brillouin-Mandelstam measurements of hard-to-reach, thermodynamic regimes in fully-sealed, CS2-filled liquid-core optical fibers. We investigate the Brillouin response in the positive and negative pressure regimes for isochoric and isobaric processes.
CRIS-Team Scopus Importer:2023-04-20

Time Dynamics of Magnon-Mediated Information Transfer from Microwave to Optical Domain - Jadhav, Rajkumar; Zeng, Xinglin; Alabbadi, Abdullah; Pal, Arghadeep; Traub, Cedric; Engelhardt, Fabian; Del'haye, Pascal; Kusminskiy, Silvia Viola; Stiller, Birgit (2025 Conference on Lasers and Electro-Optics, CLEO 2025, 2025)
We demonstrate the transfer of pulsed information from the radio-frequency to the optical domain by utilizing optomagnonic Brillouin light scattering in yttrium iron garnet microspheres. The scheme enables the study of time-dynamics of magnon-photon interactions.
CRIS-Team Scopus Importer:2025-11-21

Waveguide optomechanics – Coherent control of acoustic waves - Stiller, Birgit (Optics InfoBase Conference Papers, 2020)
Stimulated Brillouin scattering (SBS) is an optomechanical interaction involving traveling acoustic waves. In recent experiments, we demonstrated how to coherently control acoustic waves via SBS and to counteract the nanosecond acoustic decay time.
CRIS-Team Scopus Importer:2021-06-29

Widely tunable, low phase noise microwave source based on a photonic chip - Merklein, Moritz; Stiller, Birgit; Kabakova, Irina V.; Mutugala, Udara S.; Vu, Khu; Madden, Stephen J.; Eggleton, Benjamin J.; Slavik, Radan (Optics Letters, 2016)
Spectrally pure microwave sources are highly desired for several applications, ranging from wireless communication to next generation radar technology and metrology. Additionally, to generate very pure signals at even higher frequencies, these advanced microwave sources have to be compact, low in weight, and low energy consumption to comply with in-field applications. A hybrid optical and electronic cavity, known as an optoelectronic oscillator (OEO), has the potential to leverage the high bandwidth of optics to generate ultrapure high-frequency microwave signals. Here we present a widely tunable, low phase noise microwave source based on a photonic chip. Using on-chip stimulated Brillouin scattering as a narrowband active filter allows single-mode OEO operation and ultrawide frequency tunability with no signal degeneration. Furthermore, we show very low close-to-carrier phase noise. This Letter paves the way to a compact, fully integrated pure microwave source.
CRIS-Team Scopus Importer:2021-06-29